Overstatements in abstract conclusions claiming effectiveness of interventions in psychiatry: a study protocol for a meta-epidemiological investigation - Toshi A Furukawa; Kiyomi Shinohara; Hissei Imai; Nozomi Takeshima; Yu Hayasaka; Aya M Suganuma (BMJ Open, 2016)
Introduction Abstracts are the major and often the most important source of information for readers of the medical literature. However, there is mounting criticism that abstracts often exaggerate the positive findings and emphasise the beneficial effects of intervention beyond the actual findings mentioned in the corresponding full texts. In order to examine the magnitude of this problem, we will introduce a systematic approach to detect overstated abstracts and to quantify the extent of their prevalence in published randomised controlled trials (RCTs) in the field of psychiatry.Methods and analysis We will source RCTs published in 2014 from the Cochrane Register of Controlled Trials (CENTRAL) that claim effectiveness of any intervention for mental disorders. The abstract conclusions will be categorised into three types: superior (only stating significant superiority of intervention to control), limited (suggesting that intervention has limited superiority to control) and equal (claiming equal effectiveness of intervention as control). The full texts will also be classified as one of the following based on the primary outcome results: significant (all primary outcomes were statistically significant in favour of the intervention), mixed (primary outcomes included both significant and non-significant results) or all non-significant results. By comparing the abstract conclusion classification and that of the corresponding full text, we will assess whether each study exhibited overstatements in its abstract conclusion.Ethics and dissemination This trial requires no ethical approval. We will publish our findings in a peer-reviewed journal.Trial registration number UMIN000018668; Pre-results.